Experimental Investigation of Inclusion of Various Nanocarbon Black Concentrations on Mechanical Characteristics of Oil-Well Cement Slurries in High-Pressure High-Temperature Conditions - Ahmed Ebied; Sherif Fakher; Hatem Kayed (International Journal of Concrete Structures and Materials)
Abstract This study investigates the impact of adding nanocarbon black (NCB) to wellbore cement under high-pressure, high-temperature (HPHT) conditions to enhance its properties for long-term zonal isolation. Four cementitious slurries were prepared in the laboratory using the wet-mixing method, following the American Petroleum Institute standards (API 10B-2 and API 10A). NCB was incorporated as a reinforced nanomaterial in cementitious composites at varying concentrations of 0.05%, 0.1%, and 0.2% by weight of cement (BWOC) into the slurry mix fluid following a specific mixing sequence before the addition of Class-G wellbore Portland cement, which is manufactured via the dry process and commonly used in the oil and gas industry. The study evaluated parameters, such as density, rheology, free fluid (FF), fluid loss (FL), thickening time (TT), compressive strength (CS), tensile strength (TS), porosity, and permeability, following API standards. The results demonstrated that NCB additions slightly increased slurry density and significantly improved rheological properties, with low yield stress at bottomhole circulating temperatures. NCB concentrations of 0.05% and 0.1% reduced free fluid, fluid loss, and thickening time while enhancing the cement sheath's compressive and tensile strength, simultaneously reducing its porosity and permeability. Moreover, the improved early compressive strength development indicated accelerated cement hydration reactions due to incorporating NCB. The study found that 0.1% NCB was the optimal concentration, enhancing mechanical properties and operational efficiency by reducing wait-on-cement time and costs while improving wellbore integrity. However, higher NCB concentrations required careful dispersion to prevent nanoparticle agglomeration. Overall, NCB significantly enhanced cement sheath characteristics under HPHT conditions.